The role of PET/CT in the diagnosis and response assessment in patients with multiple myeloma - A. E. Pankratov; P. A. Zeynalova (Онкогематология, 2021)
A brief review focuses on the radiation diagnostics methods used in the examination of patients with myeloma and plasmacytoma. Modern imaging techniques, such as positron emission tomography combined with computed tomography (PET/CT) and magnetic resonance imaging, facilitate diagnosis and allow assessing the extent of the process and efficiency of treatment performed. Moreover, each of these methods has its own advantages and disadvantages. The most promising is PET/CT, which has sensitivity and specificity comparable to magnetic resonance imaging, while having unique advantages.